Beth’s struggle for love in Angela Morisson’s sing me to sleep - Muhammad Nur Irawan; Danu Wahyono (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research discusses about Beth’s Struggle for Love in the novel Sing Me to Sleep by Angela Morrison (2010). It aims to find out the motivation Beth’s struggle and how she struggles to get her love. Based on the result of the study, it can be concluded that the motivation focused in Sing Me to Sleep by Angela Morrison is devided into two types of motivation, namely intrinsic motivation and extrinsic motivation. In discussing Beth’s struggle for love, Suryani’s theory of struggle is applied. The theory proposes four kinds of struggle i,e. The struggle to accept the fact of life, the struggle to achieve dream, intrinsic struggle and extrinsic struggle. This research applies descriptive qualitative method with psycologhical approach. The results of the analysis shows that Beth is intrinsically motivated to struggle to be loved by doing facial surgery. After the facial surgary he transforms into a beautiful girl and this makes her feel confidence and eventually she finds her love